The Role of Mobile Devices in Appropriation of City Spaces: An Approach to the Processes of Apprehension and Use of Gyms Outdoor - Alvarez Villa, Juan Felipe; Torres Pardo, Ingrid Durley (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2017)
The main objective of this paper is to do an analysis of the role of the use of mobile devices on the appropriation of diverse areas of the city. This analysis is performed outside the research on the development of an application for mobile devices to properly use outdoor gyms in Medellín – Colombia, which has been supported by national entities such as COLCIENCIAS and COLDEPORTES; allowing to visualize the way human beings have found a new form of feeling the city.